Caracterização de um gênero de discurso diplomático: as intervenções dos representantes permanentes do Brasil, da Espanha e da França no Conselho de Segurança das Naçoes Unidas (CSNU) - Rafael Batista Andrade (2018)
The objective of this paper was to analyze four interventions of the permanent representatives of Brazil, Spain and France in the United Nations Security Council (UNSC) in the years 2011 and 2015. The analysis was carried out so as to highlight the linguistic-discursive process that characterizes this genre of institutional discourse. The French Discourse Analysis and, in particular, D. Maingueneaus researches have made up our theoretic-methodological basis. In this way, we examined the texts from the corpus with the following categories: encompassing scene, generic scene, medium, vocabulary, discursive ethos, person embrayeur, temporal-space deixis, intertext and intertextuality. These categories were complemented with other theoretical (discursive) approaches, such as A. Krieg-Planques work about institutional discourse and the Brazilian studies of French Semiotics, mainly those developed by D. L. P. de Barros and J. L. Fiorin about themes, figures and isotopies, so as to propose, in accordance with these two authors, an interdisciplinary methodology among these categories of French Semiotics (or Greimas Semiotics) and problems related to DA. The analysis of the four interventions of permanent representatives in the UNSC showed that such a discourse emerges from one of the political communication scenes, but circulates according to the very restrictions of a specific communication scene established in/by multilateral diplomatic relations inserted into a certain institutional framework. More precisely, the research revealed: a) the keyword(s) that contribute to unveil the system of restrictions of such a discourse; b) the evidence that the exploitation of diplomatic discourse themes takes place to line off historical and social aspects related to each of three States involved; c) the role of the medium in the constitution and transmutation of this discourse genre; d) the enunciators status bipartition as a member of the UNSC and as a member of a country with a particular history; e) finally, the projection of an individual ethos and a collective ethos for different purposes.